2009
DOI: 10.1007/s11629-009-0250-0
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic characteristics of hillslope and channelized debris flows: A case study in the Shitou area of central Taiwan

Abstract: The data on the hillslope and channelized debris flows in the Shitou area of central Taiwan occurred during Typhoons Toraji and Nali in 2001 were applied in this paper. The geomorphic parameters, including the flow length, gully gradient, drainage area and form factor of the debris flows were determined by spatial analysis using a Geographic Information System (GIS) based on the data derived from field investigation, aerial photographs, and topographical maps. According to such determined geomorphic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The identification of debris flows involved two basic stages. In the first stage, the possible locations of debris flow were identified from media reports (local newspapers, TV news), related documents and papers (Lin and Jeng, 2000;Cheng et al, 2005;Jan and Chen, 2005;Chen et al, 2009Chen et al, , 2012Chen, 2011), and interpretation of images, such as aerial photographs and satellite images (SPOT images before 2004; FORMOSAT2 images after 2004) to assess whether the event was classified as a debris flow. The second stage was to conduct a field investigation to confirm whether the event identified in the first stage qualified as a debris flow.…”
Section: Identification Of Debris Flow Eventsmentioning
confidence: 99%
“…The identification of debris flows involved two basic stages. In the first stage, the possible locations of debris flow were identified from media reports (local newspapers, TV news), related documents and papers (Lin and Jeng, 2000;Cheng et al, 2005;Jan and Chen, 2005;Chen et al, 2009Chen et al, , 2012Chen, 2011), and interpretation of images, such as aerial photographs and satellite images (SPOT images before 2004; FORMOSAT2 images after 2004) to assess whether the event was classified as a debris flow. The second stage was to conduct a field investigation to confirm whether the event identified in the first stage qualified as a debris flow.…”
Section: Identification Of Debris Flow Eventsmentioning
confidence: 99%
“…The soil sediments entered the stream channels and cumulated on the streambed, and then moved directly downstream in the form of channelized debris flows in rainfall periods. Several channelized debris flows that occurred in the Chen-Yu-Lan watershed during the period from 1985 to 2008 and mentioned in articles (e.g., Yu and Chen 1987;Yu 1997a, b;Cheng et al 2000Cheng et al , 2003Cheng et al , 2005Lin and Jeng 2000;Fan et al 2002;Jan and Chen 2005;Chen et al 2009) were identified by aerial photograph interpretation and field investigation, as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 97%
“…In 2001, hundreds of debris flows occurred in central Taiwan (Cheng et al 2003(Cheng et al , 2005, resulting in over 100 people dead or missing and great damage to houses, roads, bridges, and dikes. The debris flows that occurred in central Taiwan can be classified as hillslope or channelized types (Chen et al 2009). Channelized types are discussed in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Debris flow is a very rapid to extremely rapid flow of saturated debris in a deep channel, such as a gully or a ravine (Hungr et al 2001) and is usually initiated by the erosion and entrainment of hill slope and channel material by overland flow (e.g., Berti et al 2005; Thomas et al 2000;Hürlimann et al 2003;Godt and Coe 2007;Chen et al 2009) or sometimes triggered by outburst of dammed lake or reservoirs built in the channels (Zhou et al 1991;Godt and Coe 2007;Ni et al 2010bNi et al , 2012. As they have great velocity (several tens of km/h), long run-out distance (several km), and huge capacity to transport large and heavy rocks, they usually imply substantial destructive power and pose a significant hazard to people and infrastructure (Sepúlveda et al 2006;Tang et al 2011a, b, c).…”
Section: Introductionmentioning
confidence: 99%